Everything you wanted to know about the Korean language - Park, Dong-geun (The National Institute of the Korean Language, 2010)
Provides overview of the Korean language, looking at pronunciation, grammar, linguistic history and so on. Suitable for self-study, building vocabulary, and developing reading, grammar and speaking skills.